Effects of Tea Saponin Supplementation on Nutrient Digestibility, Methanogenesis, and Ruminal Microbial Flora in Dorper Crossbred Ewe - Yunlong Liu; Tao Ma; Dandan Chen; Naifeng Zhang; Bingwen Si; Kaidong Deng; Yan Tu; Qiyu Diao (Animals, 2019)
Two experiments were conducted using Dorper × thin-tailed Han crossbred ewes. In experiment 1, eighteen ewes were randomly assigned to two dietary treatments (a basal diet, or the same basal diet supplemented with 2.0 g tea saponin (TS)/head/day) to investigate the effects of TS supplementation on nutrient digestibility and methane emissions. In experiment 2, six ewes with ruminal cannulae were assigned to the same two dietary treatments as in experiment 1 to investigate the effects of TS supplementation on rumen fermentation and microbial flora. TS supplementation increased the apparent digestibility of organic matter (OM) (p = 0.001), nitrogen (N) (p = 0.036), neutral detergent fibre (NDF) (p = 0.001), and acid detergent fibre (ADF) (p < 0.001). Urinary N (p = 0.001) and fecal N (p = 0.036) output were reduced, and N retention (p = 0.001) and nitrogen retention/nitrogen intake (p = 0.001) were increased. Supplementary TS did not decrease absolute methane emissions (p = 0.519) but decreased methane emissions scaled to metabolic bodyweight by 8.80% (p = 0.006). Ammonia levels decreased (p < 0.001) and total volatile fatty acid levels increased (p = 0.018) in response to TS supplementation. The molar proportion of propionate increased (p = 0.007), whereas the acetate:propionate ratio decreased (p = 0.035). Supplementation with TS increased the population of Fibrobacter succinogenes (p = 0.019), but the population of protozoans tended to decrease (p = 0.054). Supplementation with TS effectively enhanced the apparent digestibility of OM, N, NDF, and ADF, and decreased methane emissions scaled to metabolic bodyweight.